Engineering systems acquisition and support - Mo, John P. T.; Bil, Cees; Sinha, Arvind (Woodhead Publishing in mechanical engineering., 2015)
Engineering systems such as an aircraft or frigate are highly complex and specifically designed to meet the customer's requirements. This book provides the information necessary to acquire and support complex engineering systems expected to last for a long time. Topics include: the life cycles of these systems, their design, testing and certification, and the principles behind their acquisition; operations support and logistics, systems maintenance, reliability and upgrades, and performance and risk analysis, ending with a discussion of the need for continuous improvements in these systems. The resource creates a new operational view of modern acquisition, design, services and support systems; applies enterprise modelling and analysis techniques to develop a whole systems view; takes the systems engineering approach to services system design and support. --